CPB 4. Somatic Embryogenesis in Calamansi [Citrus x microcarpa Bunge) Wijnands] using Nucellar and Endosperm (NE) Tissue at Different Stages of Development (2018)
Calamansi is one of the most important Citrus species of the Philippines. Despite the presence of numerous seeds, Filipinos still prefer to consume calamansi over lime and lemon. This study was conducted primarily to induce somatic embryogenesis in calamansi using nucellar and endosperm (NE) tissues at different stages of development. In addition, the study aimed to developed triloid calamansi lines which will result to triploid plants with seedless fruits. Results showed successful callus induction among the 30 to 60 days old NE explants with the 40 and 60 day old treatments as the best for tree 1 and tree 2, respectively. The calli were embryogenic and developed into somatic embryos undergoing stages: globular, heart, and torpedo. For both trees, the 60-day treatment had the best response in terms of somatic embryogenesis. After tree cycles of subculturing, plantlet regeneration was observed among all treatments. To establish triploid calamansi lines, the culture of the triploid endosperm is necessary. As the explants get younger, the probability of producing triploid calamansi plants increases. This study revealed that plantlets can be generated from NE explants as young as 30 days after anthesis. This increases the probability of getting triploid calamansi with seedless fruits.